GOLDEN CALF NARRATIVE: Deuteronomist Ideology of Jeroboam Reformation - Marthin Steven Lumingkewas; Jenry E.C. Mandey; Antonius Missa (Scriptura Indonesia, 2022)
Jeroboam 1st is depicted as the prototype for all future evil kings, who are regularly accused According to the books of Kings. Jeroboam accused of established two sanctuaries; Bethel and Dan to rival the temple of Solomon in Jerusalem. These shrines then provoke vehement censure and sin of Jeroboam become paradigmatic of northern apostasy. Underlying the negative depiction of Jeroboam’s cult, however, scholars have found subtle details suggesting that Jeroboam’s cult was traditional and even Yahwistic in nature. His calves may be best understood as familiar Canaanite vehicles for the invisible deity enthroned above them – in this case, Yahweh – comparable to the cherubim in southern cult of Judah. Jeroboam priesthood likely included Levites. And his choices of Dan and Bethel, too, apparently reflected a sensitivity to honor venerable memories of pre-monarchic era. This research aims to explain what Jeroboam did was not a violation of the Yahwistic system of Israel at that time. The establishment of God in Bethel and Dan did not disconcert the status of Yahweh in the treasures of Israel, instead of a form of a political assertion that separated Israel from the arrogance and the power of Judah. By using the method of analyzing historical criticism and literacy, the result is a new perspective of understanding Jeroboam’s reform in Israel - merely a political movement alone. Jeroboam never removed Yahweh from the treasury as the god of Israel. Instead, he retained Yahweh as God who was declared to have led Israel out of Egypt.